2010
DOI: 10.1124/jpet.110.173823
|View full text |Cite
|
Sign up to set email alerts
|

Buprenorphine and Opioid Antagonism, Tolerance, and Naltrexone-Precipitated Withdrawal

Abstract: The dual antagonist effects of the mixed-action -opioid partial agonist/-opioid antagonist buprenorphine have not been previously compared in behavioral studies, and it is unknown whether they are comparably modified by chronic exposure. To address this question, the dose-related effects of levorphanol, trans-(Ϫ) -3,4-dichloro-N-methyl-N-[2-(1-pyrrolidinyl)cyclohexyl] benzeneacetamide (U50,488), heroin, and naltrexone on food-maintained behavior in rhesus monkeys were studied after acute and chronic treatment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
25
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 18 publications
4
25
0
Order By: Relevance
“…This result agrees with previously published studies conducted in rats (Di Chiara and Imperato 1988; Maisonneuve et al 1994). Co-treatment with BPN (0.25 mg/kg), the lowest dose that was active behaviorally in the FST and NIH tests, prevented U50,488 from reducing DA levels supporting other reports that BPN is a potent antagonist of KORs (Richards and Sadee 1985; Leander 1987; Paronis and Bergman 2011). Moreover, BPN alone was ineffective at altering DA levels.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…This result agrees with previously published studies conducted in rats (Di Chiara and Imperato 1988; Maisonneuve et al 1994). Co-treatment with BPN (0.25 mg/kg), the lowest dose that was active behaviorally in the FST and NIH tests, prevented U50,488 from reducing DA levels supporting other reports that BPN is a potent antagonist of KORs (Richards and Sadee 1985; Leander 1987; Paronis and Bergman 2011). Moreover, BPN alone was ineffective at altering DA levels.…”
Section: Discussionsupporting
confidence: 78%
“…Drug-induced hyperactivity make the results obtained in the FST ambiguous regarding antidepressant activity since increased activity can account for the reduction of immobility. Based on BPN’s slow receptor kinetics/receptor dissociation rates and on previous studies with selective KOR antagonists like nor-BNI where behavioral testing in the FST in rats was performed 24 h after administration, BPN was subsequently tested in the mouse FST 24 h post-administration (Cowan and Lewis 1995; Carr et al 2010; Paronis and Bergman 2011). Interestingly, a single injection of BPN produced protracted antidepressant-like and anxiolytic effects lasting at least 48 h (data not shown).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Participants then received an injection of XRNTX (380 mg of naltrexone HCL gradually released from dissolvable polymer microspheres over a period of one month, manufactured by Alkermes plc, Dublin, Ireland, under the brand name Vivitrol ® ). As part of the consent procedure, participants were briefed about the loss of pharmacological effects of opioids resulting from the XRNTX treatment, and the dangers of attempting to overcome the opiate receptor blockade with higher than usual opioid doses (Paronis & Bergman, 2011; Ruan, Chen, Gudin, Couch, & Chiravuri, 2010). …”
Section: Methodsmentioning
confidence: 99%
“…As naltrexone has been shown to block morphine-mediated analgesia in mice (Yan et al, 2003) and in rats (Nielsen et al, 2008), naltrexone treatment may therefore interfere with pain-relieving medications. Furthermore, as naltrexone can precipitate withdrawal symptoms in opioid-dependent rats (Adams & Holtzman, 1990) and monkeys (Paronis & Bergman, 2011), naltrexone treatment may potentially lead to exacerbation of withdrawal-induced hyperalgesia in alcohol-withdrawn patients. Although opioid receptor agonists with highest affinity for the MOP-R, such as morphine and methadone, have been widely used in the clinic for the treatment of pain (Nissen et al, 2001;Peng et al, 2008), preclinical studies have also demonstrated that KOP-R and DOP-R both play roles in analgesia.…”
Section: Pain Perceptionmentioning
confidence: 99%